Speaking challenges and strategies in English medium instruction (EMI): Integrating language learning with vocational skills for vocational high school students - Akmal, Mohammad Mirza; Unsiah, Frida (Universitas Islam Negeri Palangka Raya, Indonesia, 2025)
English-speaking skills are essential for vocational high school students who must be prepared to communicate in globalized industries. However, despite the increasing use of English medium instruction (EMI) in vocational schools, limited research has examined the specific speaking challenges and coping strategies of students in these contexts. This study aims to explore the challenges and strategies for developing speaking skills within EMI to integrate language learning with vocational skills. This study employed an explanatory sequential design with quantitative and qualitative data. Data were collected through a questionnaire across two dimensions and interviews. One hundred students from a public vocational high school in Malang, Indonesia, participated in filling the questionnaire, with six randomly selected for interviews. Quantitative data were analyzed using SPSS and Microsoft Excel, while qualitative data underwent thematic analysis. Findings revealed internal challenges such as anxiety, limited vocabulary, and lack of practice, alongside external challenges like insufficient English-speaking programs and reliance on the mother tongue. Strategies included using language-learning apps, English media, and building social interactions. Intrinsic motivations, such as aspirations to study abroad and international friendship, also played a significant role. This study highlights the importance of creating supportive environments and provides insights for educators and policymakers in addressing students' needs.